Damage monitoring of polymer-lined carbon fibre-reinforced plastic using small-diameter fibre Bragg grating sensors. (March 2015) - Takeda, Shin-ichi; Yokozeki, Tomohiro; Ogasawara, Toshio
Small-diameter fibre Bragg grating sensors were embedded in liquid crystalline polymer-lined carbon fibre-reinforced plastics to detect internal microscopic damages that are barely visible in operation. The coupon specimen caused matrix cracks and liner debonding under tensile loading, which represented distinctive damages in a composite overwrapped pressure vessel. The reflection spectra from the fibre Bragg grating sensors were measured in the loading–unloading tests. As the number of matrix cracks increased, the width of the spectrum gradually increased. The change in the measured results were validated by spectra simulated using the axial strain distribution in the fibre Bragg grating sensor. Moreover, the influence of damage morphology on the reflection spectrum was investigated on the basis of the analytical results for both embedded and surface-bonded fibre Bragg grating sensors. The embedded fibre Bragg grating sensor was less sensitive than the surface-bonded fibre Bragg grating sensor for distinguishing among the damage modes, such as matrix cracks, liner debonding and liner failure. The effectiveness of strain-based monitoring using fibre Bragg grating sensor was demonstrated for evaluation of the microscopic damages in polymer-lined carbon fibre-reinforced plastics.